Differential Requirement of Cd8 Enhancers E8I and E8VI in Cytotoxic Lineage T Cells and in Intestinal Intraepithelial Lymphocytes - Gülich, Alexandra Franziska; Preglej, Teresa; Hamminger, Patricia; Alteneder, Marlis; Tizian, Caroline; Orola, Maria Jonah; Muroi, Sawako; Taniuchi, Ichiro; Ellmeier, Wilfried; Sakaguchi, Shinya (Frontiers in Immunology, 2019)
CD8 expression in T lymphocytes is tightly regulated by the activity of at least six Cd8 enhancers (E8I-E8VI), however their complex developmental stage-, subset- and lineage-specific interplays are incompletely understood. Here we analyzed ATAC-seq data on the Immunological Genome Project database and identified a similar developmental regulation of chromatin accessibility of a subregion of E8I, designated E8I-core, and of E8VI. Loss of E8I-core led a similar reduction in CD8 expression in naïve CD8+ T cells and in IELs as observed in E8I–/– mice, demonstrating that we identified the core enhancer region of E8I. While E8VI–/– mice displayed a mild reduction in CD8 expression levels on CD8SP thymocytes and peripheral CD8+ T cells, CD8 levels were further reduced upon combined deletion of E8I-core and E8VI. Moreover, activated E8I-core–/–E8VI–/– CD8+ T cells lost CD8 expression to a greater degree than E8I-core–/– and E8VI–/– CD8+ T cells, suggesting that the combined activity of both enhancers is required for establishment and maintenance of CD8 expression before and after TCR activation. Finally, we observed a severe reduction of CD4 CTLs among the TCRβ+CD4+ IEL population in E8I-core–/– but not E8VI–/– mice. Such a reduction was not observed in Cd8a–/– mice, indicating that E8I-core controls the generation of CD4 CTLs independently of its role in Cd8a gene regulation. Moreover, the combined deletion of E8I-core and E8VI restored CD4 CTL subsets, suggesting an antagonistic function of E8VI in the generation of CD4 CTLs. Together, our study demonstrates a complex utilization and interplay of E8I-core and E8VI in regulating CD8 expression in cytotoxic lineage T cells and in IELs. Moreover, we revealed a novel E8I-mediated regulatory mechanism controlling the generation of intestinal CD4 CTLs.